Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/13697137.2014.999660
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of red clover in alleviating menopausal symptoms: a 12-week randomized, controlled trial

Abstract: These results indicated that, compared to placebo, dried leaves of red clover were more effective in reducing the severity of menopausal symptoms in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
(31 reference statements)
0
26
1
3
Order By: Relevance
“…Furthermore, a recent randomized, placebo‐controlled clinical trial involving 72 healthy postmenopausal women revealed a significant reduction in severity of menopausal symptoms, determined by the Menopause Rating Scale (MRS). The therapy included a daily dose of two capsules with 40 mg of dried leaves of red clover, for 12 weeks …”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent randomized, placebo‐controlled clinical trial involving 72 healthy postmenopausal women revealed a significant reduction in severity of menopausal symptoms, determined by the Menopause Rating Scale (MRS). The therapy included a daily dose of two capsules with 40 mg of dried leaves of red clover, for 12 weeks …”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 99%
“…The therapy included a daily dose of two capsules with 40 mg of dried leaves of red clover, for 12 weeks. [71] Research on the effects of Trifolium plant-derived compounds on bone physiology has provided conflicting data. No beneficial effects of biochanin A administration on skeletal system were found in studies on animal model of osteoporosis.…”
Section: Clovers and Menopause-related Disorders: The Newest In-vivo mentioning
confidence: 99%
“…The glycosidic forms of isoflavones are hydrolyzed by intestinal bacteria and enzymes and further metabolized through glucuronidation within the liver [50]. Daidzein is metabolized in the liver to equol or o-desmethylangolensin (O-DMA) and genistein to pethyl phenol [51], three potent phytoestrogens derivatives that can be detected in human serum and urine [37]. In our study, S4 contains glycosidic forms of isoflavones, namely genistin, daidzin, and glycerin.…”
Section: Resultsmentioning
confidence: 88%
“…in reducing the severity of menopausal symptoms [37]. The systematic review and meta-analysis by Ghazanfarpour et al [38] concluded that consumption of red clover is effective in decreasing hot flashes, especially in women with severe hot flashes ( ≥ 5 per day).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a trial of 72 women randomly divided between placebo and 40 mg dried red clover daily for 12 weeks showed a signiicant reduction in menopausal symptoms as measured by the Menopause Rating Scale [50]. In contrast, other clinical trials have not shown a signiicant diference from placebo, particularly for hot lashes relief [5].…”
Section: Clinical Studiesmentioning
confidence: 99%